Neural Correlates of Automatic Mood Regulation in Girls at High Risk for Depression - Joormann, Jutta (2011)
Daughters of depressed mothers are at significantly elevated risk for developing a depressive disorder themselves. We have little understanding, however, of the specific factors that contribute to this risk. The ability to regulate negative affect effectively is critical to emotional and physical health and may play an important role in influencing risk for depression. We examined whether never-disordered daughters whose mothers have experienced recurrent episodes of depression during their daughters’ lifetime differ from never-disordered daughters of never-disordered mothers in their patterns of neural activation during a negative mood induction and during automatic mood regulation. Sad mood was induced in daughters through the use of film clips; daughters then recalled positive autobiographical memories, a procedure shown previously to repair negative affect. During the mood induction, high-risk girls exhibited greater activation than did low-risk daughters in brain areas that have frequently been implicated in the experience of negative affect, including the amygdala and ventrolateral prefrontal cortex. In contrast, during automatic mood regulation, low-risk daughters exhibited greater activation than did their high-risk counterparts in brain areas that have frequently been associated with top-down regulation of emotion, including the dorsolateral prefrontal cortex and dorsal anterior cingulate cortex. These findings indicate that girls at high and low risk for depression differ in their patterns of neural activation both while experiencing, and while repairing negative affect, and suggest that anomalies in neural functioning precede the onset of a depressive episode.